An Analytical Framework on Utilizing Natural Resources and Promoting Urban–Rural Development for Increasing Farmers’ Income Through Industrial Development in Rural China - Deng, Xiangzheng; Wang, Guofeng; Song, Wei; Chen, Mingxin; Liu, Yujie; Sun, Zhigang; Dong, Jinwei; Yue, Tianxiang; Shi, Wenjiao (Frontiers in Environmental Science, 2022)
Lucid waters and lush mountains are invaluable assets. The countryside is an important carrier of lucid waters and lush mountains, and rural revitalization is a national strategy and the needs of the people. Rural revitalization is a systematic and dynamic evolution. Starting from the key indicators of resource utilization and integrated urban-rural development for increasing farmers’ income through prosperous industrial development in rural revitalization, this paper constructs the framework system for improving the efficiency of resource utilization, improving the effect of urban-rural integration and optimizing the efficiency of industrial development for increasing farmers’ income. It also clarifies the challenges faced by rural revitalization, mainly including limited space for the growth of cultivated land quantity and great challenges for quality improvement, insufficient effective supply of labor resources, the uneven spatial distribution of water resources, and low utilization efficiency of agricultural water resources, etc. It finally puts forward the possible direction of future policies for rural revitalization, which is mainly reflected in the transition of resource utilization efficiency improvement from a single element to multi-element, urban-rural integration effect development from extensive to lean, industrial enrichment efficiency optimization from management to comprehensive service. The analytical framework of resource utilization, urban-rural integration development and industrial enrichment will provide regulatory policies and theoretical support for urban-rural factor flow.